Are inappropriate eating behaviors and anxiety related with track and field in adolescent athletes? - Fortes,Leonardo de Sousa (2014)
OBJECTIVE:The study analyzed the relationship between anxiety and inappropriate eating behaviors in adolescent female athletes.METHODS:Eighty-eight track and field athletes aged 12 to 17 years participated in the study. We used the Eating Attitudes Test-26 subscales to assess inappropriate eating behaviors and the Brazilian State - Trait Anxiety Inventory subscales to assess State and Trait anxiety.RESULTS:State - Trait Anxiety Inventory - State (p=0.18) or State - Trait Anxiety Inventory - Trait (p=0.14) had no significant influence on the Dieting subscale score. The Bulimia and Food Preoccupation subscale score was also not influenced by State - Trait Anxiety Inventory - State (p=0.25) or State - Trait Anxiety Inventory - Trait (p=0.21). However, State - Trait Anxiety Inventory - Trait (p=0.048) had a significant impact on the Oral Control subscale score, but State - Trait Anxiety Inventory - State (p=0.19) did not explain its variance.CONCLUSION:Only State - Trait Anxiety Inventory - Trait was related to oral control and the environmental and social forces that encourage food intake in female athletes.